2012
DOI: 10.1007/s12035-012-8234-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Complement Factor H (CFH) by Multiple miRNAs in Alzheimer’s Disease (AD) Brain

Abstract: Human brain cells rely on a specific subset of microRNAs (miRNAs or miRs) to shape their gene expression patterns, and this is mediated through microRNA effects on messenger RNA (mRNA) speciation and complexity. In recent studies (a) in short post-mortem interval Alzheimer’ disease (AD) brain tissues versus age-matched controls, and (b) in pro-inflammatory cytokine- and Aβ42 peptide-stressed human neuronal-glial (HNG) cells in primary culture, we have identified several brain-abundant miRNA species found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 59 publications
(203 reference statements)
3
165
0
1
Order By: Relevance
“…36,37 Nuclear factor-jB-regulated microRNAs are up-regulated in both AMD and Alzheimer's disease, and certain miRNAs are known to target the 3 0 -UTR of CFH, thereby down-regulating CFH. 10,38 Mir23a has also been found to be decreased in RPE cells from AMD donor eyes and has been associated with cellular resistance to oxidative stress. 26 A reduction in Dicer1 and a concomitant rise in Alu RNA has also been linked to RPE degeneration in AMD.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Nuclear factor-jB-regulated microRNAs are up-regulated in both AMD and Alzheimer's disease, and certain miRNAs are known to target the 3 0 -UTR of CFH, thereby down-regulating CFH. 10,38 Mir23a has also been found to be decreased in RPE cells from AMD donor eyes and has been associated with cellular resistance to oxidative stress. 26 A reduction in Dicer1 and a concomitant rise in Alu RNA has also been linked to RPE degeneration in AMD.…”
Section: Discussionmentioning
confidence: 99%
“…miR-146a was upregulated and acted as a biomarker in inflammatory signaling in Prion disease, Alzheimer's disease and status epilepticus. It was believed to be regulated by NF-B and contributed to inflammatory injury [17][18][19][20]. Researches about miR-146a in autoimmune diseases found that compared with healthy subjects, the expression levels of miR-146a in peripheral blood mononuclear cells (PBMC) and the synovial fluid of patients with systemic lupus erythematosus (SLE) were significantly decreased [21].…”
Section: Introductionmentioning
confidence: 99%
“…[102][103][104] CFH expression is significantly downregulated in the degenerating brain and retina, suggesting that insufficient quantities of this RCA regulator lead to excessive activation of the innate immune response and proinflammatory signaling. [105][106][107][108][109][110][111][112][113][114][115][116][117] There are many shared pathologic characteristics of Alzheimer's disease (AD) and AMD, including decreases and/or dysfunction in CFH. 118 CFH inhibits alternative pathway activation both in plasma and on cell surfaces by promoting C3b proteolysis.…”
Section: Mirnas As Regulators Of the Inflammatory Process An Importamentioning
confidence: 99%